2022
DOI: 10.3390/medicina58091233
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Optic Nerve Sheath Diameter/Eyeball Transverse Diameter Ratio in the Neurological Outcomes of Out-of-Hospital Cardiac Arrest Patients

Abstract: Background and objectives: The optic nerve sheath diameter (ONSD) is indicative of elevated intracranial pressure. However, the usefulness of the ONSD for predicting neurologic outcomes in cardiac arrest survivals has been debatable. Reportedly, the ONSD/eyeball transverse diameter (ETD) ratio is a more reliable marker for identifying intracranial pressure than sole use of ONSD. Materials and Methods: This retrospective study aimed to investigate the prognostic value of the ONSD/ETD ratio in out-of-hospital ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A retrospective study showed that the OER was a more reliable predictor of comatose status in patients with supratentorial lesions than the ONSD [ 23 ]. Cho et al [ 4 ] found that the OER was more reliable than the ONSD in predicting neurological outcomes in out-of-hospital cardiac arrest survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study showed that the OER was a more reliable predictor of comatose status in patients with supratentorial lesions than the ONSD [ 23 ]. Cho et al [ 4 ] found that the OER was more reliable than the ONSD in predicting neurological outcomes in out-of-hospital cardiac arrest survivors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed a limitation in using the ONSD alone in post-cardiac arrest patients [ 4 ]. The authors found that ONSD alone may be affected by patient characteristics and that using the ONSD/eyeball transverse diameter (ETD) ratio (OER) was more reliable.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of ultrasound has markedly increased due to various factors, including technological advances, a minimally invasive nature, affordability and the ease of use (25,26). The use of optic nerve ultrasound as an accurate, non-invasive, safe, reproducible and cost-effective ICP tool has recently been validated by the measurement of ONSD, thereby reducing the potentially deleterious consequences of invasive transcranial measurements (14,27,28). Ultrasound of the optic nerve can be used to differentiate between both normal and elevated ICP and can be a useful screening tool in resource-limited practices (29).…”
Section: Risk Of Bias Applicability Concernsmentioning
confidence: 99%